Foreign direct investment, environmental quality and economic growth in developing countries - Muhammad, Ayub (2019)
In the past few decades, foreign direct investment (FDI) appears to be instrumental for development strategies in many developing countries. FDI is believed to have an important role in promoting economic development of the host countries via technology transfer. As a result, many countries have attempted to attract more FDI inflows by relaxing regulations that limit free flows of foreign capital and providing various incentives to foreign firms. Nevertheless, not all countries have seen successful in attracting FDI inflows. Moreover, some economists are sceptical about the full impact of FDI as it may also have negative impacts on environmental quality. They argue that ignoring the potential impact of FDI on the environment may underestimate the overall effect of FDI on the host economies. The general objective of this study is to investigate the dynamic links between FDI and key macroeconomic indicators such as institutional and environmental quality as well as output growth. A battery of institutional quality indicator is employed using a sample of developing countries for the 1984-2016 period. There are three important objectives addressed in this thesis. Methodologically, a system generalized method of moments (GMM) estimator is applied to test the three objectives. The first objective of this study is to assess the determinants of FDI with a special emphasis on the complementarity effect between democracy and natural resources. This study investigates whether different types of natural resource export will have the ability to change the relationship between democracy and FDI inflows. The objective is tested using a system GMM estimator for 80 developing countries covering the 1984-2016 period. The findings reveal that democracy promotes FDI inflows in countries which exports minerals, food and agriculture raw material. Meanwhile, it reduces FDI inflows in countries that exports fuel. The finding is consistent with the view that the impact of democracy on FDI inflows depends on different type of natural resources. The second objective investigates the effect of FDI on environmental degradation with a special emphasis on the role of institutions in mitigating the environmental repercussion of FDI. A system generalized method of moments (GMM) estimator is applied to a panel of 63 developing countries using data for the 1984-2016 period. Interestingly, two important conclusions emerge. First, both pollution haven hypothesis (PHH) and environmental Kuznets curve (EKC) are valid. Secondly, the impact of FDI on environmental quality is contingent on institution such that countries with better institutional quality are able to reduce the impact of FDI on the environment. This finding is consistent with the view that attracting FDI for improving economic growth will be harmful to the environment if a proper institutional framework is not maintained. This suggests that the benefits of having more FDI inflows depend on the ability of policymakers to improve and regulate the efficiency of institutions. Moreover, the results are robust to various alternative indices for institutional quality such as index constructed by principle component analysis and exclude outlier observations. The final objective focuses on the growth-effect of FDI in 67 developing countries during 1984-2016 period, with a special attention given to the role of regime durability and regime types. Using two indicators of regime durability and three indicators of regime type, this study investigates the role of regime durability and regime types in the FDI-growth relationship. The results obtained from GMM estimation demonstrate that regime durability and regime type play crucial roles in moderating the positive effect of FDI on output growth. This suggests that marginal effect of FDI on economic growth depends on regime durability and regime type. The empirical results are robust to alternative measures of regime durability and regime type such as an index constructed using principle component analysis and average value, as well as FDI stock as an alternative measure of FDI. By and large, countries that have durable regime got more benefits from multinational corporations (MNCs) presence. This finding is consistent with the view that host countries must be able to absorb and internalize new knowledge linked to MNCs which will translate into higher output growth.